Teacher Professional Learning Community (TPLCs) on Social Studies Toward 21 st Century Learning: A Case Study of Primary Schools in Sukhothai Province, Thailand (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2017)
This research was a qualitative study aimed to improve the teachers’ teaching on social studies toward the 21st century learning of schools in Sukhothai Province, Thailand where methods of learning management were accordingly employed along with the learning in the 21st century. The data were collected from 2 schools with two administrators, twelve teachers, and one hundred students. The data collections were in-depth interview, observation, document study and focus group. The data was analyzed by content analysis. The steps of TPLCs learning were including three steps 1) plan 2) do and observe and 3) reflect. The findings showed that TPLC’s learning supports teachers in improving their practice through learning new curriculum and instructional strategies and the methods for interacting meaningfully with each child.